SOLID STATE ELECTROCHEMICAL BEHAVIOR of USNIC ACID AT A GLASSY CARBON ELECTRODE - Alves Jorge, Sonia Maria [UNESP]; Rodrigues Pontinha, Ana Dora; Matos Marques, Maria Paula; Oliveira-Brett, Ana Maria (Taylor & Francis Inc, 2010)
The electrochemical redox behavior of usnic acid, mainly known for its antibiotic activity, has been investigated using cyclic, differential pulse and square wave voltammetry in aqueous electrolyte. These studies were carried out by solid state voltammetry with the solid mechanically attached on the surface of a glassy carbon electrode and at different pH values. Usnic acid did not present any reduction reaction. The pH-dependent electrochemical oxidation occurs in three steps, one electron and one proton irreversible processes, assigned to each of the hydroxyl groups in the molecule. Adsorption of the non-electroactive oxidation product was also observed, blocking the electrode surface. An oxidation mechanism was proposed and electroanalytical methodology was developed to determine usnic acid.
Keywords: Electrochemistry; Oxidation; Solid state voltammetry; Usnic acid